Ergonomics Improvement in Ceramic Production through Hydraulic Tool Design: A Rapid Entire Body Assessment and Quality Function Deployment - Putri Noviana Nih Pratama; Sido Dea Auvia; Anggita Indriyanti; Agung Ramadhani (Universitas Serang Raya, 2026)
This study addresses ergonomic and productivity challenges in Indonesia's ornamental ceramic MSMEs. Artisans often rely on traditional tools, resulting in high musculoskeletal risks and inefficient production. Using the Nordic Body Map (NBM) and REBA, this study identified a